2 - Quand la reine-mère Dokuwa libère l’Akyem Abuakwa de la domination Ashanti - Kouamé René Allou (Afrika Zamani, 2022)
As early as 1701, the Akyem Abuakwa Akan kingdom (the best known Akan kingdom is that of Ashanti) at the confluence of Birim and Oda rivers rebelled against the swift rise of Ashanti. It therefore actively supported the irredentist Denkyira who refused to accept the defeat of their kingdom. This political choice of the Akyeme Abuakwa kings was the result of a furious conquest and hard Ashanti domination of their kingdom. The relations between Akyeme Abuakwa and Ashanti turned into open revolts followed by bloody reprisals. In 1816, after the tragic deaths of Kings Kofi Asante and Asare Bediako, Queen-mother Dokuwa took the reins of the Akyeme Abuakwa kingdom. Thanks to an intelligent strategy, she succeeded in liberating Akyem Abuakwa from Ashanti yoke.